Affective solidarity: how guilt enables cross-generational support for political radicalization in Hong Kong. (22nd December 2021) - Tang, Gary; Cheng, Edmund W.
Abstract: The extant social movement literature tends to regard the youth as radical actors and senior citizens as conservative actors. However, the Anti-Extradition Bill Movement in Hong Kong exhibited strong solidarity among protesters across generations, despite the radicalization of protest actions over an extended period. These phenomena contradict Hong Kong's traditional political culture, which favors peaceful and orderly protests and the worldwide trend where radicalization often leads to internal division in movements. By analyzing the data collected from onsite protest surveys in December 2019 and January 2020 ( N = 1, 784), this paper presents the mediating role of guilt in shifting senior citizens from opposing radical actions to supporting them and feeling solidarity with militant protesters. We find that the relationship between age and feelings of guilt is stronger among respondents who experience state repression. The findings shed light on the affective and relational dimensions of protest participation, showing how the traumatic conditions under which different social actors are welded together by shared emotional upheavals facilitate ingroup identification and affective solidarity.